(untitled) (Heritage, 2023)
Mahmut Bakali (1936 - 2006) was the president of the Presidency of the Provincial Committee of the Union of Communists of Kosovo from 1971 to 1981. He was a member of the so-called Đakovica group - Albanian communists from the vicinity of Đakovica who occupied key positions in the province of Kosovo during the entire post-war period. Bakali came to power at the time of the expansion of Kosovo’s autonomy. During his tenure, Kosovo functioned as a republic in all but name. Albanian nationalism grew, the foundations of the Albanian separatist movement were laid, the planned аlbanianization of the province took place, and the mass emigration of Serbs intensified. After his dismissal in 1981, Bakali spent almost two decades outside official politics but retained his reputation and influence among Albanians. He was a member of the Albanian delegation during the negotiations in Rambouillet in 1998, a deputy in the Assembly of Kosovo after the war in 1999, and an adviser to the Prime Minister of Kosovo, Agim Ceku. He was also a witness at the trial of Slobodan Milosevic.